Nurturing connections: advancing gender equality for improved nutrition and livelihoods - Ridolfi, Ramona (Hellen Keller International, 2019)
Presented by Ramona Ridolfi (Hellen Keller International), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.